(untitled) (Docentes 2.0 Journal, 2024)
The digital era has generated an unprecedented transformation in higher education, positioning artificial intelligence (AI) as a fundamental protagonist in this change process. This essay examines the impact of this technology in higher education, considering its respective advantages and challenges. A qualitative approach and a descriptive narrative design are adopted, using a deductive method within a humanistic paradigm. The findings conclude that the tool can potentially optimize teaching and personalize learning, which could result in more efficient and accessible education. However, despite its potential, its effective integration requires conscious and ethical consideration. The literature reviewed suggests that AI can improve educational quality, making it imperative for a comprehensive analysis to ensure its effective contribution. The essay provides a balanced view, considering the ethical and practical implications of its use to ensure that it effectively contributes to the enrichment of the educational experience.